New approach to production of antimicrobial Al2O3-Ag nanocomposites by electrical explosion of two wires. (November 2019) - Lozhkomoev, A.S.; Kazantsev, S.O.; Pervikov, A.V.; Fomenko, A.N.; Gotman, I.
Graphical abstract: Highlights: Al2 O3 -Ag nanoparticles exhibit pronounced antimicrobial activity. Nanoparticle charge affects antimicrobial activity. Electric explosion Al and Ag wires leads to the formation of Al2 O3 -Ag nanoparticles. Abstract: Antibacterial Al2 O3 -Ag nanoparticles (54 to 69 nm on average) were produced by electrical explosion of wires (EEW) in an oxygen-containing atmosphere. Silver content was varied from 23 to 74 wt% by changing the relative diameters of the Al and Ag wires. For the lowest Ag content, silver clusters less than 10 nm in size were uniformly dispersed on the surface of Al2 O3 particles. Al2 O3 -Ag nanoparticles of all the compositions carried a positive surface charge at the physiological pH = 7, as determined by zeta potential measurements. The antibacterial properties of Al2 O3 -Ag nanoparticles against both Gram-positive and Gram-negative bacteria were studied by the killing kinetics and well diffusion tests. The study revealed higher efficiency of the positively charged Al2 O3 -Ag nanoparticles against microorganisms compared to the negatively charged Ag nanoparticles produced by the same electrical explosion procedure.